A review of research on plant‐based meat alternatives: Driving forces, history, manufacturing, and consumer attitudes. Issue 5 (13th August 2020) - He, Jiang; Evans, Natasha Marie; Liu, Huaizhi; Shao, Suqin
Abstract: The topic of plant‐based meat alternatives (PBMAs) has been discussed for several decades, but it has only recently become one of the hottest topics in the food and research communities. With the purpose of investigating the current situation of scientific research on PBMA and determining future research opportunities, the driving forces for PBMA development, a brief history of its progression, key technologies required for production, and the resulting consumer attitudes are summarized. Environmental, human health, and animal welfare concerns are the main factors that have driven the development of PBMA. Although its history can trace back to ancient Asian civilizations, the first generation of PBMA originated in 1960s and a new generation of PBMA designed for carnivore was developed in recently years. Structuring methods such as extrusion and shear cell techniques have been widely studied, but improvements toward the overall appearance and flavor, biological and chemical safety control, as well as the selection of protein sources are also very important for PBMA production. The consumer acceptance of PBMA remains unsatisfactory but is continually improving. Based on those knowledge, future research opportunities include developing more effective strategies for consumer education, providing more scientific evidence for the health properties of PBMA, finding more suitable protein sources to improve the quality of the final products, improving the appearance and flavor, further examining and securing the chemical safety, exploring the structure formation mechanism during the extraction or shearing processes, and developing methods and standards for a quality evaluation of PBMA.